A journey from ethnomedicine in rural Kenya to network pharmacology using a critical research approach - Smyth, Ciara Mary (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2023)
Background: Traditional medicine (TM) is widely practiced globally, with inter-country figures on usage ranging from 30 to 90%. Research on TM is conducted for a multiplicity of reasons, among them health care and bioprospecting. Ethnodirected bioprospecting dates to the colonial era but has increased substantially over the last few decades. This thesis explored TM research beginning with historical research in West Pokot, Kenya in the 1990s, through an analysis of Carissa spinarum L. (C. spinarum), as a case study in bioprospecting research using Hunn’s phases of ethnobiology to categorise studies. Finally, a network pharmacology (NP) approach was used to study one metabolite of C. spinarum in relation to traditional therapeutics. Methods: This thesis used qualitative ethnobotanical methods in Chapter 2. Case studies of C. spinarum in chapters 3 and 4 are literature-based, using library and online databases such as PubMed. NP analysis used FAFDrugs4 for druggability screen, online databases such as PharmMapper for target predictions, Metascape for disease predictions, STRING for PPI network construction and AutoDock Vina and Gromacs 2020.1 for molecular simulations. Headspace-GC/MS was used for analysis of C. spinarum root sample (Chapter 4) and cell biology used murine iBMDM cells (Chapter 5). Results: Chapter 2 research identified 144 species with 740 use reports (URs). The most common plant families used were Fabaceae, Vitaceae and Rutaceae (28% URs); 61% of species were woody, 80% of URs used root and bark; most preparations were aqueous (81%) and 83% were taken orally. Proposed interpretations of local illness terms found malaria to be the most common illness treated (28% URs) followed by digestive and neurological disorders (19% and 16% URs). Twenty of the identified species had a significant volume of supporting cross-cultural literature including for Hoslundia opposita Vahl., Zanthoxylum chalybeum Engl., C. spinarum and Dichrostachys cinerea (L.) Wight & Arn. Chapter 3 found that C. spinarum was used across three continents, mainly in food and medicine. The documents reviewed (284) contained 513 URs, mostly from East Africa and South Asia. The majority (66%) of preparations used root and bark, were aqueous (37%) and were used orally (45%). The dominant TM use was for digestive complaints (23% URs) and infections (18% URs). Most studies (75%) presented little socio-cultural context to TM with the majority (65%) meeting criteria for Hunn Phase I, presenting decontextualised lists of plant species and their uses. Chapter 4 analysed the phytopharmacological data of C. spinarum root in relation to TM use. Ten key compounds were selected for in-depth analysis: 2’-hydroxyacetophenone (2-HAP) (2), odoroside H (4), carissone (5), (-) nortrachelogenin (6), carissanol (7), carinol (8), ursolic acid (9), rutin (10), quercetin (11), betulinic acid (12). Some demonstrated activity that potentially contributed to TM use including 6, with anti-inflammatory and antimicrobial activity while 4, a cardiac glycoside, has potential toxicity. Key activities of extracts corresponding to TM use included anti-spasmodic, anti-convulsant, anxiolytic, analgesic, and anti-HSV activities. Most studies tested organic solvent extracts (80%), in contrast to TM practice. There was a lack of metabolomic analysis of extracts (1 study) and few toxicity assessments (6 studies), limiting the usefulness of the research. Chapter 5 used NP to predict the bioactivity of 2 relative to TM use of C. spinarum root as an inhalant. Metascape analysis of predicted targets of 2 found pneumonitis, cancers and CNS disorders to be potential disease targets of 2. A case-study of 2 in pneumonitis found key intersecting targets and finally predicted that the inflammatory mediators, COX2, NOS3, MAPK14 and ALB form the most stable docking complexes with 2. Preliminary cell biology studies found that 2 inhibited the release of inflammatory mediators IFNβ, IL6. Conclusions: The results of these analyses, TM, phytopharmacological and NP research illustrate the potential for improvements at all levels towards a TM-focused ethnopharmacological research that is more ethical, relevant and successful.
APPROVED
Keywords: Traditional medicine; Bioprospecting; Carissa spinarum; Kenya; Governance of traditional medicine; Ethnopharmacology